Benign Solutions and Innovative Sequential Annealing Processes for High Performance Cu2ZnSn(Se, S)4 Photovoltaics. Issue 6 (19th November 2013) - Hsu, Chia‐Jung; Duan, Hsin‐Sheng; Yang, Wenbing; Zhou, Huanping; Yang, Yang
<x xml:space="preserve">Abstract</x> Solution‐based earth‐abundant Cu2ZnSn(Se, S)4 (CZTSSe) is proven to be a promising tool for thin‐film photovoltaic fabrication. Combining fully dissolved copper (Cu) and zinc/tin (Zn/Sn) hydrazinium constituents in an ethanolamine (EA) and dimethylsulfoxide (DMSO) solution mixture forms the CZTS precursor. All solutes in the precursor solution are intermixed on the molecular scale with excellent homogeneity. Sequential annealing steps under chalcogen vapor allow for enhanced grain growth while preventing the back contact from forming an excessively thick Mo(S, Se)2 layer. The resulting devices achieve power conversion efficiencies of 7.5% under 1 sun conditions.